Influence of Psychosocial Environment on Students' Mental Health and Intervention Strategies (Journal of Global Humanities and Social Sciences, 2025)
The psychosocial environment is closely related to students' mental health, and the complex and changing social environment has brought many psychological pressures and challenges to students. In order to effectively deal with these problems, this paper proposes a series of student mental health intervention strategies based on the impact of the psychosocial environment. These strategies include establishing a sound mental health education system, strengthening the psychological screening and early warning mechanism, creating a positive campus culture, and improving the level of mental health education teachers. Through the implementation of these strategies, colleges and universities are able to identify and solve students' psychological problems in a timely manner and provide students with more comprehensive and professional mental health services. These initiatives not only help to improve students' mental health, but also have far-reaching significance for their growth and success and future social development.